THE STUDENTS’ ANXIETY TOWARD ENGLISH LEARNING - Siti Rodiah; Neneng Islamiah (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2019)
Nowadays in Indonesia, English has been taught at school from the various levels. English is the first foreign language that becomes one of compulsory subject in Final Examination (UN). MacIntyre & Gardner (1993:284). The result of the highest and the lowest percentage of students’ preference in FLCAS questionnaire. The researcher found that 66, 7% respondents give the highest response “Strongly Agree” to statement number 5 (I start to panic when I have to speak without preparation in language class). While 11, 1% respondents give the lowest response “Strongly Agree” to the statement number 7 (I feel confident when. I speak in foreign language class). The result of this research show that most of the students are at “Anxious” level students. There are 21 (78%) students who experience “Anxious” level, 5 (19%) students are in “Mildly Anxious” level, and only 1 (4%) student from 27 students, is in “Relaxed” level.